Level versus uphill economy and mechanical responses in elite ultratrail runners - Willis, S. J.; Gellaerts, J.; Mariani, B; Basset, P.; Borrani, F.; Millet, G. P. (International Journal of Sports Physiology and Performance, 2019)
Purpose: To examine the net oxygen cost, oxygen kinetics, and kinematics of level and uphill running in elite ultratrail runners. Methods: Twelve top-level ultradistance trail runners performed two 5-min stages of treadmill running (level, 0%, men 15 km·h-1, women 13 km/h; uphill, 12%, men 10 kmh, women 9 km/h). Gas exchanges were measured to obtain the net oxygen cost and assess oxygen kinetics. In addition, running kinematics were recorded with inertial measurement unit motion sensors on the wrist, head, belt, and foot. Results: Relationships resulted between level and uphill running regarding oxygen uptake (VO2), respiratory exchange ratio, net energy, and oxygen cost, as well as oxygen kinetics parameters of amplitude and time delay of the primary phase and time to reach VO2 steady state. Of interest, net oxygen cost demonstrated a significant correlation between level and uphill conditions (r = .826, P < .01). Kinematics parameters demonstrated relationships between level and uphill running, as well (including contact time, aerial time, stride frequency, and stiffness; all P < .01). Conclusion: This study indicated strong relationships between level and uphill values of net oxygen cost, the time constant of the primary phase of oxygen kinetics, and biomechanical parameters of contact and aerial time, stride frequency, and stiffness in elite mountain ultratrail runners. The results show that these top-level athletes are specially trained for uphill locomotion at the expense of their level running performance and suggest that uphill running is of utmost importance for success in mountain ultratrail races.